(untitled) (Contemporary Journal of Social Science Review, 2026)
Artificial Intelligence (AI) is becoming more common in English teaching. It helps students learn in new ways by giving personal support and easy access to learning materials. Many people believe that AI can support fair and sustainable education. However, this idea does not fully consider important problems such as equal access, fairness, and control. Framed by the theoretical concepts of the digital divide and digital colonialism, this study looks at how AI in English teaching can both help and create challenges, especially in developing countries like Pakistan. It uses an interpretive qualitative method. Data were collected through semi-structured interviews with English teachers (n=10) and university students (n=15), complemented by a technological artifact analysis of popular AI learning tools. The results show that AI can improve student interest, independence, and language skills. However, not all students benefit equally. Students who have better access to technology and stronger digital skills gain more, while others face a secondary layer of structural exclusion. Also, many AI tools are developed in Western countries, forcing local learners to conform to foreign standards, which risks linguistic erasure and creates digital dependence. The study concludes that if AI is not used in a careful and fair way, it may reinforce social stratification rather than support fair education. It suggests using AI in ways that are more inclusive, decolonized, and suitable for local needs.